Research on Requirements of Facing Change Resistance in Damietta University from Its Faculty Members’ Points of View - Aly S. Gohar; Mayada M. F. El-Basil; Mohammed H. Gomaa (New Horizons in Education and Social Studies Vol. 9, 2021)
This research aimed to address Change Resistance phenomenon in Damietta University from its faculty members’ points of views and the requirements of facing this phenomenon. The research also examined the concept of Change Resistance and change resistance manifestations, change resistance types in Damietta University and the proposed vision to deal with this resistance. Then the research concluded to effective mechanisms through which trend towards change acceptance in Damietta University is promoted. The research analyzed change resistance reality in Damietta University by a specialized field study. The field study revealed that change resistance is the most prominent feature of the faculty members due to several reasons which are considered the major hindrance of change acceptance. The current study offered a proposed vision of change resistance requirements to promote the trend towards development and change among the faculty members of Damietta University in the light of the field study results. It also investigated the major reasons of this resistance and reasons for feeling the strength of this trend that reject change.